PENGARUH VARIABEL MAKRO DAN MIKRO TERHADAP NPL PERBANKAN KONVENSIONAL DAN NPF PERBANKAN SYARIAH - Zakiyah Dwi Poetry; Yulizar Djamaluddin Sanrego (Tazkia Islamic Finance and Business Review, 2011)
This research attempts to identify the effect of macro and micro variables to NPL (Non Performing Loan) in conventional banking and NPF (Non Performing Financing) in syariah banking. The macro and micro variables used in this research are IPI (Industrial Production Index), inflation, exchange rate, SWBI/SBIS (Sertifikat Wadiah Bank Indonesia/Sertifikat Bank Indonesia Syariah), SBI (Sertifikat Bank Indonesia), LDR (Loan to Deposit Ratio), FDR (Financing to Deposit Ratio), and CAR (Capital Adequacy Ratio).This research finds that in short run, there is no significant variables effecting NPL and NPF. In long run significant variables effecting NPL are exchange rate, IPI, inflation, SBI, LDR, and CAR and significant variables effecting NPF are lnER, lnIPI, inflasi, SBIS, FDR_BS, and CAR. According to the IRF result, this research finds that NPF in islamic banking is more stable than NPL in conventional banking to deal with macro and micro variables fluctuation. According to FEVD variables affecting NPL in conventional banking are inflation and SBI; variable affecting NPF in syariah banking is only FDR.JEL Classification: D81,G21Keywords: Non Performing Loan, Non Performing Financing